Optimalisasi Pemajuan Kebudayaan melalui Pengaturan Peran Desa Adat dalam Peraturan Daerah Provinsi Bali - Jayantiari, I Gusti Agung Mas Rwa (Jurnal Legislasi Indonesia, 2023)
Since its promulgation until now, the advancement of culture through Law Number 5 of 2017 and the regulations in the form of regional legal products under it has not optimally included participatory responsive aspects, that is the involvement of indigenous and tribal peoples with their traditional rights. In fact, houses and people are the integral parts of customary law community order, which are very visible in traditional villages in Bali which are regulated by Regional Regulation of the Bali Province Number 4 of 2019. This research aims to find out and analyze the forms of regulation concerning the role of traditional villages in Bali, especially with regard to optimizing the advancement of culture, which the government is intensely trying to realize. The government has even determined a strategy through Presidential Regulation Number 114 of 2022. The method used in this study is normative juridical with a statutory regulation approach, a conceptual approach as well as investigating legal materials. The results of the research show that the involvement of traditional villages has been determined in the provisions of Article 22 letter d of the Regional Regulation of the Bali Province Number 4 of 2019 on the formulation of duties and authorities of traditional villages, namely advancing customs, religion, traditions, arts and culture as well as local wisdom. This arrangement shows a role with a responsibility in the development and support of local culture so it can contribute to the formulation of a cultural strategy on a national scale. Keywords: Customary Law Community, Optimization, Advancement of Culture